Cover Image. (22nd August 2019) - Logie, Carmen H.; Lys, Candice L.; Dias, Lisa; Schott, Nicole; Zouboules, Makenzie R.; MacNeill, Nancy; Mackay, Kayley
Abstract : The cover image is based on the original Article "Automatic assumption of your gender, sexuality and sexual practices is also discrimination": Exploring sexual healthcare experiences and recommendations among sexually and gender diverse persons in Arctic Canada by Carmen H. Logie BA, MSW, PhD et al., DOI10.1111/hsc.12757 .